Investigation of the ergogenic effect of sodium bicarbonate ingestion on the short to medium duration high intensity cycling - Smith, B.; Donne, B. (Book of Abstracts - 9th Annual Congress European College of Sport Science, July 3-6, 2004, Clermont-Ferrand, France, 2004)
The ergogenicity associated with sodium bicarbonate (NaHCO3) loading is primarily attributed to induced alkalosis offsetting the metabolic acidosis produced during short to medium duration high intensity exercise. Published research indicates that the response to NaHCO3 ingestion is dependent on dosage (Matson & Tran, 1993), type and duration of exercise, study population (Kozak-Collins et al., 1994) and the time delay from ingestion to commencement of exercise (Linderman & Fahey, 1991). However, several studies have reported no ergogenic effect following NaHCO3 ingestion (Housh et al., 1991; Linderman et al., 1992; Stephens et al., 2002). The present study investigated the ergogenic effect of NaHCO3 ingestion on 5-km time trial performance in male road-racing cyclists and additionally the reproducibility of the ergogenic effect. Methods Trained male amateur road-racing cyclists (n=10, mean±SD; age 30±3 yr, mass 78±4 kg, height 179±4 cm, % fat 15±3%) volunteered to undertake simulated 5km time-trials, in a double-blinded study design, 80-min following pre-loading with NaHCO3 (300 mg.kg-1), NaCl (207 mg.kg-1) or lactose (207 mg.kg-1). To investigate the reproducibility of the ergogenicity of NaHCO3 ingestion volunteers were pre-loaded with NaHCO3 on two separate occasions. Volunteers completed each of the four 5 km time trials on a standard road-racing bicycle fitted with a laboratory grade SRM power-crank (SRM Ltd., Germany) and mounted on a hydraulically resisted turbo-trainer (Elit-Travel Hydroforce Ltd., Italy). Heart rate (HR) data were continuously recorded by radio telemetry (Cardiosport Ltd., Taiwan) and blood lactate (BLa) data in mmol.L-1 (YSI Ltd., USA) were recorded from fingertip blood samples collected pre-, mid (at 2.5 km) and post (at 5km), split times and mean power output were also recorded at 1 km intervals. Data were analysed using a repeated measures ANOVA model, post-hoc analysis of significant differences were quantified using Student-Newman-Keuls test, values of P<0.05 were considered statistically significant. Reproducibility of data following NaHCO3 ingestion was assessed using interclass correlation coefficients (ICC 3,1). Results Performance times for the simulated 5km time-trials were significantly faster (P<0.05) following NaHCO3 ingestion; the mean decreases were 16.3 and 16.4s compared with NaCl and 13.0 and 12.9s compared with lactose, respectively, no significant differences were recorded comparing NaCl and lactose. The mean decreases in performance times equated to distances of 156 and 126 m compared to NaCl and lactose, respectively. Analysis of I km split times revealed that NaHCO3 exerted a cumulative ergogenic effect across the entire time trial, which was not accentuated over any 1 km interval. No significant differences in BLa data were recorded at 0 or 2.5 km, however, significantly higher BLa data were recorded at 5km, mean BLa post-test were 15.7±4.0 and 15.6±3.7 mmol.L-1 following both NaHCO3 trials compared with12.1±2.9 and 13.2±1.2 mmol.L-1 following NaCl and lactose. No significant differences in HR data were detected across treatment groups at 1km intervals, mean HR data at 5km were 185±12, 184±13 beats.min-1 following both NaHCO3 trials compared with 184±13 and 183±12 beats.min-1 following the NaCl and lactose trials. Analysis of reproducibility of 5km time-trial performance times following NaHCO3 ingestion yielded a high correlation coefficient ( ICC 3,1=0.977). Discussion NaHCO3 ingestion 80 min pre-exercise significantly improved 5 km time-trial performance and the ergogenic effects of NaHCO3 ingestion were highly reproducible. Post-test lactate data indicated that the induced alkalosis facilitated increased lactic acid efflux from the active musculature allowing for a sustained increase in power output across the entire 5km time-trial.